Tissue-engineered cartilage regeneration based on human induced pluripotent stem cells - LI Yangyang; ZHANG Maolin; ZOU Duohong; ZHANG Zhiyuan (Kouqiang hemian waike zazhi)
[Objective:] To establish a stable and efficient culture approach for guiding human induced pluripotent stem cells (hiPSCs) differentiation towards chondrogenic mesodermal lineage, and preliminarily explore the possibility of hiPSCs-derived cartilaginous pellets for articular cartilage regeneration. [Methods:] By simulating the development process in vivo, hiPSCs were gradually induced to differentiate into chondrogenic mesodermal lineage and mature cartilage using three dimensions (3D) suspension culture system. Real-time quantitative polymerase chain reaction(RT-qPCR), Western blotting, immunofluorescence and immunohistochemistry were used to investigate the dynamic expression change of pluripotent, mesodermal and chondrongenic related genes and proteins during the whole culture procedure. Finally, subcutaneous model of nude mice was used to investigate the stability of chondrogenic phenotypes and tumorigenicity of hiPSCs derived-cartilaginous pellets. [Results:] By simulating the development process in vivo, hiPSCs were gradually induced to differentiate into chondrogenic mesodermal lineage, and finally differentiated into mature cartilage tissues. [Conclusion:] In this study, a stable and efficient culture approach for inducing hiPSCs differentiation towards chondrogenic mesoderm was successfully established, which provide a research platform for investigation of hiPSCs-mediated cartilage development and regeneration.